Prevalence, Distribution And The Biology Of An Endoparasitoid Fly, Verticia fasciventris (Diptera: Calliphoridae), And The Physiological And Behavioural Changes In Its Host, Macrotermes carbonarius (Blattodea: Termitidae) - To, Thi Mai Duyen (2018)
This thesis focuses on prevalence, distribution and the biology of an endoparasitoid fly, Verticia fasciventris Malloch (Diptera: Calliphoridae) and the physiological and behavioural changes in its host Macrotermes carbonarius (Hagen) (Blattodae: Termitidae). The development of V. fasciventris larvae could be divided into three instar stages. The larva completed their first and second instar in the head capsule of M. carbonarius pre-soldier and soldiers, respectively, while the third instar undergoes part of its development inside the head of soldiers and subsequently exit the host body as free living larva. The mean time of pupation of V. fasciventris was 13 days. The size of parasitoid females was significantly smaller (P < 0.05) than that of males.